Institutions, holdup and automation - Presidente, Giorgio (CESifo, Center for Economic Studies & Ifo Institute, 2019)
This paper documents a positive relationship between labor-friendly institutions and investment in industrial robots in a sample of advanced economies. Institutions explain a substantial proportion of cross-country variation in automation. The relationship between institutions and robots is stronger in sunk cost-intensive industries, where producers are more vulnerable to holdup. This suggests that automation is used by producers as a tool to thwart rent appropriation by labor.
10419/207225
Keywords: Graue Literatur; automation; robots; holdup; institutions; unions; sunk costs; appropriability; bargaining; frictions; rents; technology adoption